Fluorescence Polarization Assay for the Diagnosis of Anti-Brucella abortus Antibodies in Cattle Serum: Adaptation for its Use in Microplates and Comparison with Conventional Agglutination Tests - Gutiérrez, Silvina Elena (2014)
Bovine brucellosis, which is endemic in Argentina, is controlled by vaccination and slaughter of infected cattle. Conventional agglutination tests and primary binding assays like ELISA and fluorescence polarization assay (FPA) are used for the identification of infected cattle. The FPA has many advantages over the agglutination tests, however most accredited laboratories still use the conventional agglutination tests. FPA has been extensively evaluated in its original format of 10mm x 75mm glass tubes, while there are little reports on its performance in the 96-well microplate format. The aim of the present study was to set the conditions for the use of a commercially available antigen (the O-polysaccharide from B. abortus 1119-3 conjugated with fluorescein isothiocyanate) for the FPA assay in a 96-well microplate format, and to compare its diagnostic performance with the conventional agglutination tests currently used in Argentina. Serum samples were obtained from 149 cows and 20 bulls belonging to free and infected herds from different regions of Argentina. Two dilutions of serum and antigen were assayed and the fluorescence polarization was detected with a Beckman DTX 880 multimode reader.